c-Myc-induced sensitization to apoptosis is mediated through cytochrome c release - Juin, Philippe (Cold Spring Harbor Laboratory Press, 1999)
Expression of c-Myc sensitizes cells to a wide range of pro-apoptotic stimuli. We here show that this pro-apoptotic effect is mediated through release of mitochondrial holocytochrome c into the cytosol. First, activation of c-Myc triggers release of cytochrome c from mitochondria. This release is caspase-independent and blocked by the survival factor IGF-1. Second, c-Myc-induced apoptosis is blocked by microinjection of anticytochrome c antibody. In addition, we show that microinjection of holocytochrome c mimics the effect of c-Myc activation, sensitizing cells to DNA damage and to the CD95 pathway. Both p53 and CD95/Fas signaling have been implicated in c-Myc-induced apoptosis but neither was required for c-Myc-induced cytochrome c release. Nonetheless, inhibition of CD95 signaling in fibroblasts did prevent c-Myc-induced apoptosis, apparently by obstructing the ability of cytosolic cytochrome c to activate caspases. We conclude that c-Myc promotes apoptosis by causing the release of cytochrome c, but the ability of cytochrome c to activate apoptosis is critically dependent upon other signals.